The Effect of Literal Comprehension on the Higher Levels of Comprehension in Reading Skill: A Longitudinal Case Study - Ratih Laily Nurjanah; Salma Rafita Putri (Universitas Muhammadiyah Semarang, 2022)
Comprehension in reading skill is generally divided into 4; literal, interpretive, critical and creative which has different indicators and types of questions from one to another. Literal reading, as the lowest level of comprehension is considered important to be mastered by students before they work with higher level of comprehension. This is a longitudinal case study aims to explain the effect of literal reading mastery on the higher levels. This study involved 15 students of English Literature students observed since they were in 1st semester to 4th semester. The instruments used are working sheets to measure students’ ability in each level of comprehension. The findings showed that students with good and very good mastery of literal comprehension worked good on interpretive, critical and creative level. The students with poor mastery of literal comprehension did not have good results on interpretive, critical and creative level. It revealed that literal comprehension has important role in building students’ comprehension before they continue to the next levels.